IMPLEMENTASI MODEL PEMBELAJARAN INQUERY LEARNING DENGAN MEDIA PEMBELAJARAN TTS UNTUK MENUMBUHKAN PEMAHAMAN PADA SISWA KELAS 8 MTS NU HASYIM ASY’ARI 2 KUDUS - Afifatut Thohiroh; Siti Wulandari; Vani Dwi Safitri; Dany Miftah M. Nur (ARIMA : Jurnal Sosial Dan Humaniora, 2024)
This research aims to implement the Inquiry Learning learning model with crossword puzzle (TTS) learning media to improve the understanding of class VIII students at MTS NU Hasyim Asy'ari 2 Kudus. The method used in this research involved analyzing data from 26 students, consisting of 17 men and 9 women, as well as teachers who taught Social Sciences subjects. The results of the research show that students can draw conclusions from the problems formulated with the help of guiding questions from the teacher. Apart from that, students can also present their conclusions and make applications from the knowledge they have gained through the assignments given. The application of TTS media in learning has proven effective in growing students' understanding, where they are actively involved in the learning process and are able to test and deepen their understanding of the material being studied. It is hoped that this research can contribute to the development of more interactive and fun learning methods.   .